2020
DOI: 10.1186/s40942-020-00239-8
|View full text |Cite
|
Sign up to set email alerts
|

OCT changes of idiopathic epiretinal membrane after cataract surgery

Abstract: Background: We reviewed our experience in the management of cataract and idiopatic epiretinal membrane surgeries at the Humanitas Research Institute-Milan, Italy-over the past 3 years. Methods: We conducted a single center retrospective observational case series of patients that underwent sequential cataract and idiopatic epiretinal membrane (ERM) surgeries from 2012-2015 in Humanitas Research Institute. Full data was obtained for 53 eyes of 57 patients. Patients with ERM secondary to uveitis or trauma or asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…6,8,18,19 A previous report identified phacoemulsification as a significant risk factor. 21 Conversely, the comparison of the functional and anatomical outcomes of combined phacoemulsification/vitrectomy and vitrectomy only yielded similar results. 22 The association between phacoemulsification and ELM/EZ alteration cannot be explained solely by the longer time of the surgerybecause the procedure length was considered in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 92%
“…6,8,18,19 A previous report identified phacoemulsification as a significant risk factor. 21 Conversely, the comparison of the functional and anatomical outcomes of combined phacoemulsification/vitrectomy and vitrectomy only yielded similar results. 22 The association between phacoemulsification and ELM/EZ alteration cannot be explained solely by the longer time of the surgerybecause the procedure length was considered in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 92%
“…A study conducted by Vallejo-Garcia et al [ 22 ] reported no statistically significant correlation between the stage of ERM and the development of CME. Their investigation utilized the Govetto classification and analyzed postoperative variables 1 month after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated increased rates of cystoid macular oedema (CMO) following cataract surgery in eyes with preexisting ERM compared with those without ERM. 11,[19][20][21] In the study by Schaub et al,15.7% of eyes with preexisting ERM developed postoperative CMO compared with only 5.9% of eyes without ERM. 11 Similarly, the retrospective study by Hardin et al, involving 812 eyes with ERM and 159,184 reference eyes, found that eyes with ERM were at significantly higher risk of postoperative CMO compared with eyes without ERM (8.6% versus 1.38%, respectively).…”
Section: Specific Pathologies To Consider Epiretinal Membranementioning
confidence: 99%